Implementation of Quality by Design (QbD) Approach in Development of QCT-SMEDDS with Combination of AgNPs for Diabetic Foot Ulcer Management - Badhwar, Reena; Singh, Ruchi; Tinku; Popli, Harvinder (Indian Journal of Pharmaceutical Education and Research, 2021)
Introduction: Quercetin (QCT) is a flavonoid with antioxidant, potential free radical scavenger, and strong anti-inflammatory activities. These properties of QCT promote wound healing process. Objectives: The present work to investigate the diabetic wound healing efficacy of QCT- loaded self-micro emulsifying drug delivery system (QCT-SMEDDS) and Silver nanoparticles (AgNPs) in combination. Materials and Methods: The QCT-SMEDDS were develop and optimized using D-Optimal design mixture by observing numerous critical qualities attributes (CQAs). A pseudo ternary phase diagram was constructed using Transcutol HP, PEG 400 and oleic acid. The developed formulation evaluated for in vivo and stability studies. Further, prepared formulation was characterized for globules size, in vitro drug release, antimicrobial, ex vivo permeation, skin deposition, and pharmacokinetics studies in diabetic wound model. The optimized formulation showed globules size, polymer dispersive index (PDI) and zeta potential of QCT-SMEDDS were found to be 101.7nm with PDI 0.17 and -29.2 mV respectively with improved release rate (92%) due to enhanced solubility of QCT in the form of SMEDDS. Silver nanoparticles (AgNPs) were combined with QCT-SMEDDS to enhance the antimicrobial effects and for better wound healing. The combination of QCT and AgNPs were developed in an emulgel and various physiochemical characterization and evaluation of emulgel were carried out. In vitro, ex vivo studies using dialysis membrane and Strat-M respectively. In-vivo experiment including % wound contraction and histopathological studies (rate of re-epithelization) of emulgel and marketed gel were performed using diabetic excision wound model. Results: Presented that emulgel has better wound contraction and rate of re-epithelialization as compared to marketed gel. Further histopathological study of skin including rate of re-Epithelization were carried out and found that this gel help to stimulates fibroblast and granulocytosis formation that leads to eschar and keratin layer formation which is a good sign of healing. Conclusion: The present study that the AgNPs-QCT incorporated emulgel has been projected as a potential substitute for the topical delivery of QCT in the treatment of diabetic foot ulcer (DFU).
Keywords: Diabetic foot ulcer; QCT-SMEDDS; Silver nanoparticles; Strat-M; Wound contraction; Histopathology